Evaluation of Sézary cell marker expression and cell death behaviour upon in vitro treatment by flow cytometry in Sézary syndrome patients - Melchers, Susanne; Römer, Mathis; Albrecht, Jana Dorothea; Assaf, C.; von Gugelberg, C.; Guenova, E.; Klemke, C.-D.; Moritz, R. K. C.; Schlaak, M.; Stadler, R.; Wehkamp, U.; Wobser, M.; et al. (Experimental dermatology, 2024)
The diagnosis of Sézary syndrome (SS) relies on the identification of blood Sézary cells (SC) by different markers via flow cytometry. Treatment of SS is challenging since its pathogenesis is characterized by cell death resistance rather than hyperproliferation. In this study, we establish an integrated approach that considers both the expression of SC markers and sensitivity to cell death both spontaneously and upon in vitro treatment. Peripheral blood mononuclear cells were isolated from 20 SS patients and analysed for the SC markers CD7 and CD26 loss as well as CD158k and PD1 gain. The cells were then treated with different established and experimental therapies in vitro and cell death was measured. Spontaneous and therapeutically induced cell death were measured and correlated to cellular marker profiles. In the marker-positive cells, spontaneous cell death sensitivity was reduced. Different treatments in vitro managed to specifically induce cell death in the putative CTCL cell populations. Interestingly, a repeated analysis after 3 months of treatment revealed the CTCL cell death sensitivity to be restored by therapy. We propose this novel integrated approach comprising the evaluation of SC marker expression and analysis of cell death sensitivity upon treatment that can also enable a better therapy stratification.
Online veröffentlicht: 1. September 2024
Gesehen am 28.10.2024